Dynamic Balance Optimization of an Ultra High-speed Packaging Machine based on a Micro Multi-objective Genetic Algorithm - Hu Bo; Chen Guochun; Li Huijie; Zhou Changjiang (Jixie chuandong)
To improve the dynamic performance of the pusher device in an ultra high-speed packaging machine,the optimization design and analysis on dynamic balance are performed. Based on the multi-rigid-body dynamics theory,a dynamic model of the pusher device is established. Major components for producing inertia force and torque are acquired according to the dynamic model. The equations of shake force and torque are derived by building a mathematical model for the components. Taking the root-mean-square of shake force and torque into account,dynamic balance of the components with variables of mass and barycentre location is optimized based on a micro multi-objective genetic algorithm. According to the optimal value of variables,the structure of the pushing hands is redesigned. After optimization,the shake force and torque of the packaging machine are reduced by 23. 6% and 29. 5% respectively,and natural frequency of pushing hands is not close to260 Hz anymore. The results show that dynamic performance of the pusher device is improved obviously and the resonance is avoided.